Needle Stick/Sharp Injuries in Health Care Workers - Abida Sultana, Afifa Kulsoom, Rahim Iqbal (Journal of Rawalpindi Medical College, 2014)
Background: To assess the pattern of the needle stick / sharp injuries (NSI) in health care workers (HCW) and to assess post injury action in HCW after being pricked. Methods: This hospital based cross sectional descriptive study was conducted on 116 conveniently selected health care workers (HCW) including doctors, nurses and paramedics. Accidental needle-stick injury (NSI) was defined as a prick with a needle or other sharp object during use of the object for patient care. The parameters of pattern of NSI included frequency of NSIs in preceding 12 months, source of the prick injury, procedure during which prick was sustained. The parameters of post exposure response included action after the prick, post exposure testing. Results: Majority (70.6%) of HCW were accidently pricked at least once in the past 12 months. The most common source of prick injury was found to be needle (80.49%). The most common procedure during which the respondents were accidently pricked was during drawing of blood (41.16%) and the least common procedure was found to be during breaking vials (12.20%). After the prick 27% respondents did nothing, 33% did wound dressing, 35% did wound toilet, and 5% went for immunization. Males are pricked considerably more often as compared to females. Conclusion: Needle stick/sharp injury is a major problem in HCW of tertiary care hospitals of Rawalpindi. The most common procedure is drawing blood and most common source is needle by which they get pricked. The population at high risk is of house officers, and males are more commonly pricked than females.